The dilemmas and transformations that involve motherhood in the contemporary female context: The dilemmas and transformations that involve motherhood in the contemporary female context - Godinho Gomes, Bruna Katerine; Silva, Kerolyn Rodrigues da; Saraiva, Odara Lélis Leal; Oliveira, Pâmela Scarlatt Durães (Revista Unimontes Científica, 2023)
Objective: to describe the dilemmas and transformations that involve motherhood in the contemporary female context. Methodology: this is a descriptive research with a qualitative approach carried out from 2020 to 2021 with fifty mothers registered in a basic health unit in a municipality in the north of Minas Gerais. A script of guiding questions was used for data collection. Data were collected through digital instruments such as meet and Google Forms. The speeches were analyzed through content analysis. Results: the results pointed to a reality of difficulties and pleasures. The speeches show that the interviewees need more support in the care of their children so that they can resume their usual activities after maternity. Final considerations: it is considered that the objective of the study was achieved due to the possibility of evaluating the whole process experienced by the woman after becoming a mother, how much the woman is psychologically affected in the postpartum period, due to the changes and transformations in her life, in the body, desires, functions and thoughts.